Perbadanan Kemajuan Negeri Perak / Mohd Wafiq Zainal Abidin ... [et al.] - Zainal Abidin, Mohd Wafiq; Shalan, Shairul Nizam; Abdullah, Mohd Syafiq Dannial; Mohd Nawi, Nur Shalsabila; Jafar, Nurfazielah Nazierah (Universiti Teknologi Mara, Perak, 2016)
Perbadanan Kemajuan Negeri Perak ( PKNP ) is classified as a government office building. In this chapter explain the description details of property for PKNP building. In this chapter also include the building background that explain about the building background in details. Besides that, its explain the project brief that involve when the building construction started until the construction finished, building view that is related to the orientation of the building, location plan that explain on where building can be found on map, and also the adjacent building that have around the building. Furthermore, other content that have in this chapter is property description where it is will describe the current state of property. Next, the building accommodation is also include that explain on the each floor in detail, the facilities that provide in and out of the building also include in this chapter. Finally all of the sub-topic above is summarize at the end of the chapter. The Perbadanan Kemajuaan Negeri Perak (PKNP) that is located at No.1-A, Block A Jalan Meru Casurina, Bandar Meru Raya, 30020 Ipoh, Perak and its also nearby Bandar Meru Raya. The building have two tower which is namely by Tower A and Tower B. both tower consist 8 floors and there did not have any basement in this building.